A convenient synthesis of short-chain α-(1 → 2) mannopyranosyl oligosaccharides. (March 2020) - Zhang, Wenhui; Wang, Jun; Serianni, Anthony S.; Pan, Qingfeng
Abstract: Sugar 1, 2-orthoesters are by-products of chemical glycosylation reactions that can be subsequently rearranged in situ to give trans glycosides. They have been used as donors in the synthesis of the latter glycosides with good regio- and stereo-selectivity. Alkyl α-(1 → 2) linked mannopyranosyl disaccharides have been reported as the major products from the rearrangement of mannopyranosyl orthoesters. Recent studies in this laboratory have shown that α-(1 → 2) linked mannopyranosyl di-, tri- and tetrasaccharides can be obtained in one step from mannopyranosyl allyl orthoester under optimized reaction conditions. In addition to the expected mono- and disaccharides (56%), allyl 2, 3, 4, 6-tetra- O -acetyl-α-d -mannopyranosyl-(1 → 2)-3, 4, 6-tri- O -acetyl-α-d -mannopyranosyl-(1 → 2)-tri- O -acetyl-α-d -mannopyranoside and allyl 2, 3, 4, 6-tetra- O -acetyl-α-d -mannopyranosyl-(1 → 2)-3, 4, 6-tri- O -acetyl-α-d -mannopyranosyl-(1 → 2)-3, 4, 6-tri- O -acetyl-α-d -mannopyranosyl-(1 → 2)-3, 4, 6-tri- O -acetyl-α-d -mannopyranoside were obtained in 23% and 6% isolated yields, respectively, from the oligomerization of a β-d -mannopyranosyl allyl 1, 2-orthoester, along with small amounts of higher DP oligomers. Possible mechanisms for the oligomerization and side reactions are proposed based on NMR and mass spectrometric data. Graphical abstract: Image 1 Highlights: A facile synthetic route to short-chain α-(1 → 2) mannopyranosyl oligosaccharides. Mechanisms of orthester rearrangement transformation and concurrent side-reactions. An easy access to di- and trisaccharide precursors for high-mannose N-glycans.